Role and mechanisms of autophagy, ferroptosis, and pyroptosis in sepsis-induced acute lung injury - Shen, Yao; He, Yingying; Pan, Ying; Liu, Li; Liu, Yulin; Jia, Jing (Frontiers in Pharmacology, 2024)
Sepsis-induced acute lung injury (ALI) is a major cause of death among patients with sepsis in intensive care units. By analyzing a model of sepsis-induced ALI using lipopolysaccharide (LPS) and cecal ligation and puncture (CLP), treatment methods and strategies to protect against ALI were discussed, which could provide an experimental basis for the clinical treatment of sepsis-induced ALI. Recent studies have found that an imbalance in autophagy, ferroptosis, and pyroptosis is a key mechanism that triggers sepsis-induced ALI, and regulating these death mechanisms can improve lung injuries caused by LPS or CLP. This article summarized and reviewed the mechanisms and regulatory networks of autophagy, ferroptosis, and pyroptosis and their important roles in the process of LPS/CLP-induced ALI in sepsis, discusses the possible targeted drugs of the above mechanisms and their effects, describes their dilemma and prospects, and provides new perspectives for the future treatment of sepsis-induced ALI.